GAMBARAN FAKTOR RISIKO KEJADIAN ANEMIA PADA BALITA - Lani Gumilang; Devi Nurlaelasari; Meita Dhamayanti; Rd. Tina Dewi Judistiani; Neneng Martini; Akhmad Yogi Pramatirta (JKM (Jurnal Kebidanan Malahayati), 2021)
Background: Anemia is a condition in which the hemoglobin is below the normal value. According to Riskesdas, anemia in toddlers in 2018 was 38.5%. Many factors cause anemia in toddler, such as gender, birth weight, history of premature birth, history of exclusive breastfeeding, nutritional status and mother's education. Purpose: This study aims to determine the description of the risk factors for the incidence of anemia in toddler.Methods: This study uses secondary data in the form of a cohort with a total sampling of 53 toddler in Cirebon Regency. The analysis used in this research is univariate analysis. Results: In this study, it was shown that Toddler with anemia were seen from risk factors, namely female sex as much as 55.2%. Normal birth weight is 57.4%. Good nutritional status (BB/U) was 55.1% and Toddler short nutritional status (TB/U) were 66.6%. Those who do not have a history of exclusive breastfeeding are 60.8%, and have a history of being premature as much as 60% and with a mother's education not attending school as much as 100%Conclusion: Female gender, Toddler with short nutritional status and a history of premature birth and mothers with low education are more likely to experience anemia than other risk factors. Suggestion It is necessary to provide counseling to parents of toddlers regarding risk factors for the incidence of anemia in toddlers, especially in toddlers with female gender and toddlers experiencing stunting. Keywords: Anemia, Toddler, Risk Factor ABSTRAK Latar belakang: Anemia adalah suatu kondisi di mana hemoglobin berada dibawah nilai normal. Menurut Riskesdas anemia pada balita tahun 2018 yaitu sebesar 38,5%. Banyak faktor yang menyebabkan anemia pada balita, seperti jenis kelamin, berat badan lahir, riwayat prematur, riwayat ASI Eklusif, status gizi dan pendidikan ibu.Tujuan: Penelitian ini bertujuan untuk mengetahui gambaran faktor risiko kejadian anemia pada balita.Metode: Penelitian ini menggunakan data sekunder berupa kohort dengan total sampling sebanyak 53 balita di Kabupaten Cirebon. Analisis yang digunakan pada penelitian ini adalah analisis univariat.Hasil: Dalam penelitian ini menunjukan bahwa balita yang mengalami anemia dilihat dari faktor risiko yaitu jenis kelamin perempuan sebanyak 55,2%. Berat badan lahir normal yaitu 57,4%. Status gizi baik (BB/U) sebanyak 55,1% dan balita status gizi pendek (TB/U) yang mengalami anemia sebanyak 66,6%. Yang tidak memiliki riwayat ASI eklusif sebanyak 60,8%, dan memiliki riwayat prematur sebanyak 60% serta dengan pendidikan ibu tidak sekolah sebanyak 100%Kesimpulan: Jenis kelamin perempuan, balita dengan status gizi pendek dan memiliki riwayat prematur serta ibu yang berpendidikan rendah lebih banyak yang mengalami anemia dibandingkan faktor risiko lainnya.Saran perlu dilakukan penyuluhan pada orang tua balita mengenai faktor risiko kejadian anemia pada balita terutama pada balita dengan jenis kelamin perempuan dan balita yang mengalami stunting. Kata kunci : Anemia, Balita, Faktor Risiko